Discourses of Indigenous-Christian Elites in Colonial Societies in Asia and Africa around 1900: A Documentary Sourcebook from Selected Journals - Koschorke, Klaus (Dokumente zur Außereuropäischen Christentumsgeschichte, 2016)
Cover -- Title Page -- Copyright -- General Table of Contents -- Preface -- A. General Introduction -- B. Selected Journals From Four Regions -- I. India (edited by Klaus KOSCHORKE) -- II. South Africa (edited by André SAENGER and Ciprian BURLACIOIU) -- III. West Africa (edited by E. Phuti MOGASE and Frieder LUDWIG) -- IV. The Philippines (edited by Adrian HERMANN) -- C. Supplement -- D. Appendix -- Klaus KOSCHORKE, General Introduction: Goals of the Entire Research Project and the Present Text Selection -- General Structure of the Sourcebook -- 1. Introduction